Remotely monitored telerehabilitation for cardiac patients: A review of the current situation - Batalik, Ladislav; Filakova, Katerina; Batalikova, Katerina; Dosbaba, Filip (World journal of clinical cases, 2020)
Cardiac rehabilitation through center-based programs is an effective multicomponent intervention for the secondary prevention of cardiovascular diseases. Despite the benefits it brings, patients' participation in rehabilitation programs remains low. In this work, the latest relevant literature regarding remotely monitored cardiac telerehabilitation (TR) was reviewed considering its efficiency and utilization. The main objective was to assess whether TR has the potential to be an appropriate alternative form of rehabilitation. A total of 105 publications on this topic were screened out of 747 full-text articles that were read and evaluated, of which 12 were considered suitable for inclusion in the final review. Feasibility, efficiency, and safety were assessed for each TR intervention. The results of our evaluation indicate that TR seems to be a usable, effective, and safe alternative rehabilitation for patients with heart disease. Most of the currently published articles have studied remotely monitored TR intervention offering a comprehensive approach, which indicates the significant development and steps forward in this field of study. Our research evidence supports the implementation of TR, which could positively influence barriers in participating in cardiac rehabilitation programs.
Keywords: Telecoaching; Cardiac rehabilitation; Telemedicine; Wearable devices; Telemonitoring; Cardiovascular diseases; Telerehabilitation